More Recent Wheat Cultivars Extract More Water from Greater Soil Profile Depths to Increase Yield in the Texas High Plains. (1st November 2017) - Thapa, Sushil; Xue, Qingwu; Jessup, Kirk E.; Rudd, Jackie C.; Liu, Shuyu; Pradhan, Gautam P.; Devkota, Ravindra N.; Baker, Jason
Abstract : Core Ideas: We investigated the depth and amount of soil‐water extraction in TAM wheat cultivars. Yield was largely related to soil‐water extraction under dryland conditions. Relatively newer cultivars were able to extract more water from deeper soil profile. Drought is the most important factor limiting wheat ( Triticum aestivum L.) yield in the U.S. southern High Plains (SHP). Adoption of suitable cultivars and crop management practices are crucial to reducing yield loss from drought in the area. We conducted a 5‐yr study to investigate the depth and amount of net soil water extraction (SWE) in four wheat cultivars at different growth stages. Plants were grown under dryland conditions and volumetric soil water content (SWC) was measured in 0.2‐m increments to the depth of 2.4 m at planting, jointing, anthesis, and maturity. There were large variations in grain yields (474–3685 kg ha −1 ) in dryland wheat across years and cultivars. Yield was largely determined by plant available soil water (PASW) at planting and seasonal precipitation. In a season with high yield (3548 kg ha −1 in 2016), net SWE occurred in the whole 0.0‐ to 2.4‐m profile. In contrast, in a season with very low yield (650 kg ha −1 in 2011), net SWE was limited to the upper 1.2 m. More recent cultivars (TAM 110, TAM 111, and TAM 112) were able to extract more water from deeper in the soil profile (particularly between jointing and maturity), and had higher evapotranspiration (ET), biomass, and yield than the legacy wheat cultivar (TAM 105), especially during the dry seasons of 2011 and 2012. This study demonstrated that effective use of soil water from greater soil depths is important for greater ET and yield under dryland conditions in a semiarid environment.